SN 2024hpj: A perspective on SN 2009ip-like events - Salmaso, I.; Pastorello, A.; Borsato, E.; Benetti, S.; Botticella, M. T.; Cai, Y. -Z.; Elias-Rosa, N.; Farina, A.; Fraser, M.; Galbany, L.; González-Bañuelos, M.; Gutiérrez, C. P.; et al. (EDP Sciences, 2026)
Supernovae (SNe) IIn are terminal explosions of massive stars that are surrounded by a dense circumstellar medium (CSM). Among SNe IIn, a notable subset is the SN 2009ip-like, which exhibits an initial, fainter peak attributed to stellar variability in the late evolutionary stages, followed by a brighter peak, interpreted as the SN explosion itself. In this context, we analysed the spectrophotometric evolution of SN 2024hpj, an object with a triple-peaked light curve and spectra typical of a SN IIn but with a complex line profile composed of broad P-Cygni features topped by narrow emissions. Comparing it with other SN 2009ip-like events in the literature, as well as with other unpublished objects (SNe 2019mry, 2022ytx, 2024uzf, and 2025csc), we identify star-forming regions as their preferred formation environment. On the other hand, the diversity of spectrophotometric features within the sample suggests that variations in CSM mass and distribution may influence the observed characteristics. We identify four sub-classes based on the luminosity and rapidity of the light curve evolution, which provides insights into possible differences in the progenitors, while a statistical analysis of their observed rate indicates progenitor masses around 25 − 31 M⊙ or lower.